Euro area equity risk premia and monetary policy: A longer-term perspective - Daniel Kapp; Kristian Loft Kristiansen (European Central Bank (ECB), 2021)
This study analyses the effects of euro area monetary policy on equity risk premia (ERP). We find that changes in equity prices during periods of accommodative monetary policy mainly reflected adjustments in the discount factor and economic activity - rather than fluctuations in investors' required risk compensation. Furthermore, the ERP appears to not have declined much since the introduction of unconventional monetary policy and stands higher than prior to the GFC. Use of identified monetary policy shocks points to insignificant effects of monetary policy on the ERP. Further breakdown of these shocks reveals that monetary policy has a significant upwards impact on the ERP if it is perceived as a negative information surprise, while the opposite prevails in the case of a genuine accommodative monetary policy surprise. Accumulating these effects over time suggests that the two might have largely offset each other since the introduction of unconventional monetary policy.
Keywords: E22; E52; G12; 330; monetary policy transmission; monetary policy shocks; equity risk premia